Tilapia head glycolipids reduce inflammation by regulating the gut microbiota in dextran sulphate sodium-induced colitis mice. Issue 4 (27th March 2020) - Gu, Zhipeng; Zhu, Yujie; Jiang, Shuaiming; Xia, Guanghua; Li, Chuan; Zhang, Xueying; Zhang, Jiachao; Shen, Xuanri
Abstract : Tilapia head glycolipids reduce inflammation by regulating the gut microbiota in dextran sulphate sodium-induced colitis mice. Abstract : In this study, we evaluated the effects of tilapia head glycolipids (TH-GLs) on male C57BL/6 mice with inflammatory bowel disease (IBD) induced by dextran sulfate sodium (DSS) and the changes in gut microbiota compared with sulfasalazine. Mice were orally treated with 3% (w/v) DSS or not for 7 days, followed by drug treatment with TH-GLs or sulfasalazine. After treatment, macroscopic colitis symptoms, intestinal epithelial barrier function, inflammatory cytokines, and gut microbiota homeostasis were assessed. Further studies showed that TH-GLs and sulfasalazine showed different influences on the gut microbiota structure. Both sulfasalazine and TH-GLs decreased the DSS-induced enrichment of Gammaproteobacteria and Enterobacteriaceae . However, TH-GLs had a selective increase in the enrichment of Akkermansia, Prevotellaceae, Oscillospira, Allobaculum, Bifidobacterium, and Coprococcus in contrast to sulfasalazine, which selectively increased the enrichment of Dorea, Turicibacter, Bacteroides, Coprobacillus, Mucispirillum, and Dehalobacterium . In addition, both TH-GLs and sulfasalazine relieved body weight loss, and increased the immune organ index, while maintaining the balance between pro-inflammatory and anti-inflammatory cytokines. The results indicate that TH-GLs alleviate DSS-induced IBD in mice by decreasing the abundance of harmful gut microbiota and enhancing the abundance of probiotic gut microbiota. Thus, the mechanism through which TH-GLs inhibit inflammation through gut microbiota is different from that of sulfasalazine. Therefore, TH-GLs stand as potential prebiotics for the treatment of colonic inflammation and related diseases.